The correlation of depression with neglect and abuse in individuals over 65 years of age - Aylaz, Rukuye; Pekince, Hatice; Isik, Kevser; Akturk, Ummuehan; Yildirim, Hilal (Wiley, 2020)
PurposeThis study was conducted to evaluate the correlation of neglect and abuse with depression in individuals over 65 years of age. Design and MethodsThis descriptive study included 290 elderly people who were registered at 10 family health centers in Turkey. FindingsIt was determined that mental health problems were present in the sample, and elderly individuals were exposed to abuse and neglect. The levels of depression were found to be high in elderly individuals with no spouses, low level of education, low income, living with their children and unable to access personalized care. The depression levels were also found to be high in the elderly individuals who were subjected to abuse and neglect. Practical ImplicationsAwareness of healthcare professionals is of great importance in preventing abuse and neglect experienced by elderly individuals.
Keywords: abuse and neglect; elderly people; geriatric depression